An empirical study on the promotion of city economic growth by the healthy development of real estate and land finance - Qian, Hua; Sun, Qian; Li, Min; Liu, Yisong; Li, Fangya (Frontiers in Sustainable Cities, 2024)
This paper is based on panel data from 278 prefecture-level cities in China from 2012 to 2021, and studies the relationship between healthy real estate development, land finance, and economic growth. The findings indicate that there are distinct trends in the healthy development of real estate across different city levels in China. By using the PVAR model, the intrinsic connections between real estate health, industrial transformation and upgrading, and economic growth are revealed. The results from the heterogeneity analysis show that the lag periods of real estate health, land finance, and economic growth have a positive impact on themselves in municipalities, provincial capitals, and prefecture-level cities. In prefecture-level cities, there is a significant interactive promotion between healthy real estate development and land finance. Land finance can directly contribute to economic growth, forming a "land finance-economic growth" direct effect channel. Additionally, healthy real estate development has a significant positive impact on promoting economic growth.